2017
DOI: 10.1167/iovs.16-21170
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a p38 Mitogen-Activated Protein Kinase Inhibitor on Cellular Senescence of Cultivated Human Corneal Endothelial Cells

Abstract: Citation: Hongo A, Okumura N, Nakahara M, Kay EP, Koizumi N. The effect of a p38 mitogen-activated protein kinase inhibitor on cellular senescence of cultivated human corneal endothelial cells. Invest Ophthalmol Vis Sci. 2017;58:3325-3334. DOI:10.1167/iovs.16-21170 PURPOSE. We have begun a clinical trial of a cell-based therapy for corneal endothelial dysfunction in Japan. The purpose of this study was to investigate the usefulness of a p38 MAPK inhibitor for prevention cellular senescence in cultivated hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 40 publications
0
39
0
Order By: Relevance
“…15 Even if cultured HCECs do not acquire these fibroblastic changes, they can undergo senescence, which decreases the cell density and again produces cells that are not applicable for clinical use. 16 An additional complication is that the proliferative ability of HCECs is limited even under ideal culture conditions, so multiple procedures have been developed to promote cell proliferation. [29][30][31][32] For instance, we reported that the use of a ROCK inhibitor, 13 conditioned medium derived from mesenchymal stem cells, 14 and laminin 511 fragment as a culture substrate 17 enhances cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…15 Even if cultured HCECs do not acquire these fibroblastic changes, they can undergo senescence, which decreases the cell density and again produces cells that are not applicable for clinical use. 16 An additional complication is that the proliferative ability of HCECs is limited even under ideal culture conditions, so multiple procedures have been developed to promote cell proliferation. [29][30][31][32] For instance, we reported that the use of a ROCK inhibitor, 13 conditioned medium derived from mesenchymal stem cells, 14 and laminin 511 fragment as a culture substrate 17 enhances cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Corneal endothelial growth medium was prepared by conditioning basal medium mix (OptiMEM-I, 8% fetal bovine serum [ 14,16 Briefly, confluent 3T3 fibroblasts were incubated with 4 lg/mL mitomycin C (MMC) (Kyowa Hakkko Kirin Co., Ltd., Tokyo, Japan) for 2 hours, seeded on plastic dishes at a cell density of 2 3 10 4 cells/cm 2 , and cultured with DMEM (Life Technologies Corp., Grand Island, NY, USA) supplemented with 10% FBS, 100 U/mL penicillin, and 100 lg/mL streptomycin (Nacalai Tesque, Inc., Kyoto, Japan). The 3T3 fibroblasts were washed 3 times with PBS and cultured with basal medium mix for an additional 24 hours.…”
Section: Cell Culturesmentioning
confidence: 99%
See 3 more Smart Citations